Pengaruh Profitabilitas, Ukuran Perusahaan dan Kepemilikan Manajerial Terhadap Manajemen Laba Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Tampubolon, Okta Emelia; Hidayat, Taufik; Harefa, Kornelius (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2023)
The purpose of this study is so determine the effect of Profitability, Company Size and Managerial Ownership on Earnings Management in Manufacturing Companies Listed on Indonesia Stock Exchange Period 2018 “ 2019. This sample selection using purposive sampling method. Base on predetermined criteria, 38 companies was obtained so that the observation data amounted to 76. The data analysis techniques use were descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of this study indicate that partially Profitability and Company Size have no significant effect on Earnings Management whereas Managerial Ownership has a significant effect on Earnings Management. Simultaneously, Profitability, Company Size and Managerial Ownership have a significant effect on Earnings Management.